Identification of B-lymphotropic papovavirus-coded proteins. - Segawa, K (1983)
The lymphotropic papovavirus (LPV)-specific mRNAs were translated in vitro in rabbit reticulocyte lysates. The specific products were 84,000-dalton (84K), 41K, 35K, and 26K proteins. Immunoprecipitation with anti-LPV hamster sera and analysis of partially purified LPV virions showed that the last three proteins were the LPV capsid proteins, and we designated the 41K, 35K, and 26K proteins VP1 (major capsid protein), VP2, and VP3, respectively. Several characteristics, such as the small amount of mRNA for the 84K protein at late stages of infection, its absence from partially purified virus preparations, no common tryptic peptides between the 84K and 41K proteins, and the pattern of in vivo phosphorylation, suggest that the 84K protein is not a simple dimer of the 41K protein. Normal human sera and sera from certain leukemic patients positive for antibody to LPV viral antigens immunoprecipitated the 41K protein.